Letter from Carl D. Duncan to Patricia Whiting, June 6, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan outlines plans for a trip to Mt. Lassen and thanks Whiting for her companionship.